Tearing with mastication in relation to facial paralysis: a case report of the crocodile tears syndrome - Fróis, Ana Teresa (2022)
Introduction: Abnormal lacrimation with mastication is an uncommon complaint, which may follow paralysis of the facial nerve of any cause. The mechanism behind this symptom is not clearly established, and there is no consensus about the best treatment option. This case highlights the role of family doctors in patient education and reassurance, fundamental for acceptance and management of the emotional impact associated. Case report: Male, 56 years old. Presented to his family doctor in February 2020 complaining of crying every time he ate. This affected only the left eye and started a year before, while the patient was undergoing rehabilitation therapy for peripheral facial paralysis secondary to an acoustic neuroma removal surgery. Profuse nasal congestion affecting only the left nostril occurred simultaneously.  The left side of the face showed a higher muscle tone than the right. Symptoms began concurrently with the recovery of motor function. At the follow-up neurosurgery consultation, the patient mentioned the abnormal tearing and was told that it was a sequela of his lesion which required no further investigation. The patient wanted to know more about this symptom and what could be done to solve it, so he consulted his family doctor. The diagnostic hypothesis was explained to the patient and treatment options were briefly approached. The patient felt that an invasive procedure was unnecessary and felt reassured by the diagnosis. Comments: Even though lachrymation while eating is not so impactful as facial paralysis as a sequela of acoustic neuroma surgery, it is associated with a great emotional burden on patients, who frequently avoid social eating. Sufficient information should be provided to the patient, as it may be enough to give the patient relief, or, if treatment is needed, the patient should be correctly oriented.